2013
DOI: 10.1016/j.pscychresns.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptors in post-mortem brains of Cloninger type 1 and 2 alcoholics: A whole-hemisphere autoradiography study

Abstract: Dysfunction of the brain glutamate system has been associated with alcoholism. Ionotropic glutamatergic alpha-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptors (AMPARs) play an important role in both neurotransmission and post-synaptic plasticity. Alterations in AMPAR densities may also play a role in the neurobiological changes associated with alcoholism. In the present study, [(3)H] AMPA binding density was evaluated in the nucleus accumbens (NAc), frontal cortex, anterior cingulate cortex (ACC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
(70 reference statements)
3
12
0
Order By: Relevance
“…To sum, two out of the three studies showed that the expression of AMPA receptors increased in the hippocampus of the patients with AUD, while the other failed to show changes . A decreased receptor binding or expression in this region of the patients with AUD was identified in two of three studies that examined the amygdala, and no change was found for the cocaine and heroin abusers in the other study .…”
Section: Other Substance Use Disordersmentioning
confidence: 86%
See 4 more Smart Citations
“…To sum, two out of the three studies showed that the expression of AMPA receptors increased in the hippocampus of the patients with AUD, while the other failed to show changes . A decreased receptor binding or expression in this region of the patients with AUD was identified in two of three studies that examined the amygdala, and no change was found for the cocaine and heroin abusers in the other study .…”
Section: Other Substance Use Disordersmentioning
confidence: 86%
“…With respect to the putamen, two studies to target cocaine abusers and patients with AUD showed no change, whereas overexpression of receptors was observed in the study on heroin abusers . In the frontal cortex, there was no difference among both two studies that investigated patients with AUD . As for the cingulate cortex, binding of AMPA receptor was higher in the Cloninger type 2 AUD patients in one study, whereas there was no significant change in the study for the patients with AUD .…”
Section: Other Substance Use Disordersmentioning
confidence: 92%
See 3 more Smart Citations